EDUKASI DAN IMPLEMENTASI PEMANTAUAN JENTIK UNTUK MENGURANGI KASUS DEMAM BERDARAH DENGUE DI DESA PONDOK - Gatra Azzuma Wicaksana; Hasan Mujaddid; Shelsa Mutiara Sukma; Agelia Rizky Jayanti; Rohimah Ismatullah; Az Zahra Rajwa T; Adinda Riska Permata; Dewi Nur Sifa F B; Kysea Alea; Virgitha Pramesti A; Endah Cahya Mursiam; Amara Wahyu Alfina (Jurnal Berkawan: Jurnal Pengabdian kepada Masyarakat, 2025)
Dengue Fever or Dengue is a viral disease transmitted by mosquitoes that has spread rapidly throughout the region. The dengue virus is transmitted by female mosquitoes, especially the Aedes aegypti species. Pondok village, Grogol District, Sukoharjo Regency, is ranked first with the highest dengue fever rate in the district. Given this problem, the solution provided is health education about dengue fever and monitoring larvae in the home environment which aims to reduce cases of dengue fever in Pondok Village. The method used is the method we use in this research is analysis of events from facts that we have obtained in the field. With the permission and recommendation of the health center, the Group 2 Real Work Lecture group carried out education and implemented larva checking in residents' homes, which was carried out door to door. The village's hope for the community is to avoid all diseases and consistently maintain a clean and healthy lifestyle